Determinasi Terpaan Media dan Motif Penggunaan terhadap Kepuasan Informasi di Platform Instagram - Maulidia, Rafiqa; Nurmaningsih, Nurmaningsih; Nissrina, Novia Eka (Journal of Trends Economics and Accounting Research, 2025)
The development of communication technology and the increasingly massive use of social media, where media such as Instagram plays an important role in the rapid and effective dissemination of information. The Instagram account @infobogor is a platform that focuses on delivering local information in the Bogor area, West Java, such as the latest news, traffic conditions, weather, regional activities, as well as local social and government issues. This study aims to analyze whether there is an influence of media exposure and media usage motives on the satisfaction of followers of the @infobogor Instagram account regarding news in the Bogor area. This study uses a quantitative method. There were 100 respondents, who were active followers of the @infobogor Instagram account. The sampling technique used was probability sampling. The questionnaire and data were processed using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, T-tests, F-tests, and coefficient of determination tests. Based on the T-test and F-test, the variables of media exposure and media usage motives had a positive partial and simultaneous effect on the satisfaction of followers of the @infobogor Instagram account regarding news coverage in the Bogor area. The coefficient of determination indicates that there is an influence of media exposure and media usage motives on the satisfaction of followers of the @infobogor Instagram account regarding news coverage in the Bogor area, namely 62.6%, which indicates a strong level of influence.